Enhancing Well-being and Sustainable Agricultural Development in Sawahan Turen Village: A Comprehensive Analysis of Rural Population's Welfare and Agricultural Economics - Novirin, Barli; Sidharta, Iwan; Herlambang, Adi (P3M, STIE Pasundan, Bandung, Indonesia., 2024)
Unforeseeable and fluctuating seasons can result in diminished agricultural yields, irregular rainfall patterns that adversely affect crop growth, and subpar harvests. The presence of pests and diseases can have a substantial impact on crop health and productivity, leading to decreased yields and lower-quality crops. Additionally, the rising costs of fertilizers and other agricultural inputs can impede farmers' ability to acquire essential resources, thereby hampering their productivity and overall profitability. The aim of this study is to assess the well-being of the rural population in Sawahan Turen Village, specifically focusing on the agricultural sector. The study aims to identify the challenges faced by the community in carrying out agricultural activities and to explore the strategies that can be implemented in agricultural economics to improve the well-being of the community in Sawahan Turen Village. By examining these aspects, the study aims to provide valuable insights and recommendations for promoting sustainable agricultural development and enhancing the overall welfare of the community. This study employs a qualitative approach, utilizing both primary and secondary data to support the research objectives. The research is conducted in Sawahan Turen Village, with primary data collected through direct interviews with key subjects and informants, including farmers in Sawahan Turen Village, agricultural extension workers, and relevant stakeholders. Through this qualitative approach, the study aims to provide valuable insights and recommendations for sustainable agricultural development and improving the overall welfare of the community. The research findings highlight the significant role of the agricultural sector in Sawahan Turen Village in contributing to the well-being of its community. It was observed that the involvement of the youth in this sector is notable, as a considerable number of young individuals in Sawahan Turen Village engage in farming activities. The primary reasons for their participation in agriculture are the profitability of farming in the village and the inheritance of agricultural land from their parents, which has equipped them with the necessary farming skills passed down through generations. Interestingly, despite having higher levels of education, many young individuals in Sawahan Turen Village choose to pursue farming. This has contributed to the continuity and preservation of the agricultural sector in the village, which has been practiced and sustained for generations. The study's originality is derived from its specific focus on Sawahan Turen Village, examining the agricultural sector's impact on community well-being. While previous research exists on rural development, this study offers a unique perspective by investigating youth involvement in farming and the preservation of traditional practices. By uncovering the motivations behind youth engagement, including profitability and inherited land, the study sheds light on the sustainability and dynamics of agriculture in Sawahan Turen Village. This contributes to a broader understanding of the relationship between agriculture, youth participation, and rural community well-being. While this study offers valuable insights, it is important to acknowledge its limitations. These include the specific focus on Sawahan Turen Village, potential biases in qualitative research methods, the limited timeframe, and the singular perspective of the youth. Future research should address these limitations for a broader understanding.